The Urban Land, the Disputed Land: The Land Disputes of Pawirorejo in Surakarta 1982-1985 - Styawan, Aris Agus (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2024)
Abstract: The issue of land disputes in urban areas during the New Order era intensified due to the massive use of land for housing needs and to support various development projects. Especially in the late 1970s, land issues had become a major concern in cities at the municipal level. This paper analyzed the causes of land disputes involving the Pawirorejo family in the city of Surakarta. This historical research used archival sources such as trial documents from the Surakarta Court Office, regional statistical data, and newspapers. The study's results suggest that the state-controlled lands in Surakarta, which did not receive full attention, triggered the Pawirorejo land dispute; consequently, the city government's weak control also played a role. Furthermore, land as a commodity with significant value in the city of Surakarta is vulnerable to conflicts, and the adage